Dynamic processes of mindfulness-based alterations in pain perception - Lu, Chen; Moliadze, Vera; Nees, Frauke (Frontiers in Neuroscience, 2023)
Mindfulness-based processes have been shown to enhance attention and related behavioral responses, including analgesia, which is discussed as an effective method in the context of pain interventions. In the present review, we introduce the construct of mindfulness, delineating the concepts, factors, and processes that are summarized under this term and might serve as relevant components of the underlying mechanistic pathways in the field of pain. We also discuss how differences in factors such as definitions of mindfulness, study design, and strategies in mindfulness-based attention direction may need to be considered when putting the findings from previous studies into a whole framework. In doing so, we capitalize on a potential dynamic process model of mindfulness-based analgesia. In this respect, the so-called mindfulness-based analgesia may initially result from improved cognitive regulation strategies, while at later stages of effects may be driven by a reduction of interference between both cognitive and affective factors. With increasing mindfulness practice, pathways and mechanisms of mindfulness analgesia may change dynamically, which could result from adaptive coping. This is underlined by the fact that the neural mechanism of mindfulness analgesia is manifested as increased activation in the ACC and aINS at the beginner level while increased activation in the pINS and reduced activation in the lPFC at the expert level.